Zambia - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
An updated debt sustainability analysis (DSA) is prepared using the revised Low-income Countries Debt Sustainability Framework (LIC DSF) to assess Zambia’s current debt situation. Debt burden indicators have deteriorated considerably since the October 2017 DSA mainly on account of large fiscal deficits as the authorities made use of available financing to boost infrastructure spending, weaker growth and exchange rate, and a worsened external environment (terms of trade and financial conditions). Rising debt service costs (both externally and domestically) and a large pipeline of contracted and to-be-disbursed loans place Zambia’s public debt on an unsustainable path under current policies while budget expenditure arrears have risen. Zambia’s debt-carrying capacity has also weakened with its FX reserves’ import coverage declining from 4.7 months in 2015 to 1.7 months in May 2019. All four external debt burden indicators breach their indicative thresholds, three of them by large margins and throughout the medium-term under the baseline scenario. Total public debt is projected to increase somewhatin the near-term as, under unchanged policies, fiscal deficits remain large, before gradually declining as large debt-financed public projects are completed and forced fiscal adjustment occurs given financing constraints. As a frontier market, Zambia’s high gross financing needs (peaking at 19 percent of GDP over the next three years), combined with wide EMBI spreads (1,575 basis points on June 11, 2019) and high domestic borrowing costs, expose it to significant market-financing risks. Despite the challenging fiscal situation, Zambia has remained current on all its debt obligations both domestic and external, and has not experienced a debt distress event. The authorities remain committed to prioritizing debt service payments and have identified resources to continue meeting debt obligations in the near-term. However, staff assess the risk of external and overall public debt distress for Zambia as very high at this juncture, and that a large upfront and sustained fiscal adjustment is essential to begin reducing debt vulnerabilities.